2021
DOI: 10.1097/txd.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-reperfusion Injury in the Transplanted Lung: A Literature Review

Abstract: Lung ischemia-reperfusion injury (LIRI) and primary graft dysfunction are leading causes of morbidity and mortality among lung transplant recipients. Although extensive research endeavors have been undertaken, few preventative and therapeutic treatments have emerged for clinical use. Novel strategies are still needed to improve outcomes after lung transplantation. In this review, we discuss the underlying mechanisms of transplanted LIRI, potential modifiable targets, current practices, and areas of ongoing inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 200 publications
1
27
0
1
Order By: Relevance
“…In our study, 2 patients (No.3 and 5) underwent bilateral lung transplantation. Primary graft dysfunction, which was a very common postoperative complication, was similar to ARDS ( Talaie et al, 2021 ). However, these two patients were all on the fifth day after the operation when the esophageal balloon catheter were placed, and the chest X-ray results also showed that the infiltration in both lungs had been obviously absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 2 patients (No.3 and 5) underwent bilateral lung transplantation. Primary graft dysfunction, which was a very common postoperative complication, was similar to ARDS ( Talaie et al, 2021 ). However, these two patients were all on the fifth day after the operation when the esophageal balloon catheter were placed, and the chest X-ray results also showed that the infiltration in both lungs had been obviously absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2a safety trial on the use of allogeneic mesenchymal stem cells for the treatment of moderate to severe ARDS was published in 2019, reporting an acceptable safety profile [124]. These promising results are generalizable to the lung transplant population and provide a basis for clinical trials evaluating the efficacy of mesenchymal stem cells in the treatment of pulmonary IRI in lung transplantation [125,126]. Recently, several mesenchymal stem cell therapies for chronic lung allograft dysfunction have been reported.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…A number of pre-transplant and donor-related risk factors are associated with LIRI and the development of PGD [14]. Studies of transplant outcomes have shown that during the first 24 h post-transplantation, donor factors predominate [15] whereas recipient risk factors are more influential beyond 24 h [16].…”
Section: Pretransplant/donor Risk Factors For Pgdmentioning
confidence: 99%
“…For this reason, ischemic durations beyond 8 h are a limitation to successful transplantation and must be factored into consideration prior to a transplant decision [10]. The aforementioned efforts to protect the lungs are helpful, but they do not protect the lungs from injury during the reperfusion phase at the time of transplantation [14].…”
Section: Procurement and Cold Static Preservation: Gold Standard Preservation Strategies Contribute To Primary Graft Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation